2002
DOI: 10.1016/s0378-1097(01)00556-0
|View full text |Cite
|
Sign up to set email alerts
|

Direct detection of N-acylhomoserine lactones in cystic fibrosis sputum

Abstract: Pseudomonas aeruginosa and Burkholderia cepacia cause destructive lung disease in cystic fibrosis (CF) patients. Both pathogens emploỳ quorum sensing', i.e. cell-to-cell communication, via diffusible N-acyl-L-homoserine lactone (AHL) signal molecules, to regulate the production of a number of virulence determinants in vitro. However, to date, evidence that quorum sensing systems are functional and play a role in vivo is lacking. This study presents the first direct evidence for the presence of AHLs in CF sputu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 16 publications
5
73
1
Order By: Relevance
“…aeruginosa has evolved into one of the most common and refractory nosocomial pathogens of immunocompromised patients due to its resistance to many antibiotics and a pre-dilection to colonise surfaces, especially injured epithelium, in a biofilm form, orchestrated by intercellular 'quorumsensing' signalling molecules (QSM) [34,35]. The endobronchial presence of QSM was demonstrated in both colonised CF patients [36][37][38][39] and in clinically stable, though possibly colonised, LTx recipients [40]. QSM have an intrinsic immunomodulatory capacity resulting in suppressed T-cell proliferation, neutrophil chemotaxis and chemokine (especially IL-8) or cytokine release from bronchial epithelial cells [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…aeruginosa has evolved into one of the most common and refractory nosocomial pathogens of immunocompromised patients due to its resistance to many antibiotics and a pre-dilection to colonise surfaces, especially injured epithelium, in a biofilm form, orchestrated by intercellular 'quorumsensing' signalling molecules (QSM) [34,35]. The endobronchial presence of QSM was demonstrated in both colonised CF patients [36][37][38][39] and in clinically stable, though possibly colonised, LTx recipients [40]. QSM have an intrinsic immunomodulatory capacity resulting in suppressed T-cell proliferation, neutrophil chemotaxis and chemokine (especially IL-8) or cytokine release from bronchial epithelial cells [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…These results provide a strong functional correlation between LPS modification enzyme levels and the LPS structural modifications seen in this environmental condition, confirming the validity of ICAT analysis. A number of P. aeruginosa virulence factors are regulated by quorum sensing bacterial communication via small molecule signals N-(3-oxododecanoyl)-L-homoserine lactone (3OC12-HSL) and N-butyryl-L-homoserine lactone (C4-HSL) [24,25,26,13]. The quantitative protein profiles indicated that magnesium limitation induced several quorum sensing proteins including the 3OC12-HSL synthase LasI [27] and the starvation and general stress-response regulator RelA [28,29] (Table 2).…”
Section: Quantitative Proteomic Analysis Defined P Aeruginosa Virulementioning
confidence: 99%
“…In P. aeruginosa, two acyl-homoserine lactone-based systems, the las and rhl systems, have been described (10,12,14). Apart from its quorum-sensing function, the P. aeruginosa N-3-oxododecanoyl-homoserine lactone (3-oxo-C 12 -HSL) autoinducer has been suggested to modulate the immune responses of the infected host.…”
mentioning
confidence: 99%